The ghost job - Van Eekhout, Greg (Harper, an imprint of HarperCollinsPublishers, 2023)
"Zenith and her friends may be dead--but lucky for them, even getting ghosted wasn't enough to tear them apart. The four of them were thick as thieves long before an unfortunate lab accident sent them careening into the afterlife. So when they hear about a machine that could return them to the land of the living, they are determined to steal it. Unfortunately, the magical device belongs to a dangerous necromancer who's out for their ectoplasm. Fortunately, they're great at heists. Because pulling off the score of their deathtimes is no job for an amateur"--